Nanostructured Metal Oxide Semiconductors towards Greenhouse Gas Detection - Mehran Dadkhah; Jean-Marc Tulliani (Chemosensors, 2022)
Climate change and global warming are two huge current threats due to continuous anthropogenic emissions of greenhouse gases (GHGs) in the Earth’s atmosphere. Accurate measurements and reliable quantifications of GHG emissions in air are thus of primary importance to the study of climate change and for taking mitigation actions. Therefore, the detection of GHGs should be the first step when trying to reduce their concentration in the environment. Throughout recent decades, nanostructured metal oxide semiconductors have been found to be reliable and accurate for the detection of many different toxic gases in air. Thus, the aim of this article is to present a comprehensive review of the development of various metal oxide semiconductors, as well as to discuss their strong and weak points for GHG detection.